FACTORS TO ENSURE THE QUALITY OF EDUCATIONAL WORK IN PRESCHOOL EDUCATIONAL ORGANIZATION - Mahpuza Abdurahmanova (Galaxy International Interdisciplinary Research Journal, 2021)
The article discusses the factors related to improving the quality of education in preschool education. In particular, special attention is paid to the planning of the educational process, the level of training required of the educator.